Asian economic growth and management accounting / Akira Nishimura - Nishimura, Akira (Faculty of Accountancy & Accounting Research Institute (ARI), 2002)
This study is intended to investigate Asian management accounting practices in relation to economic growth. In order to clarify the features of management accounting practices in Asian countries, the development of management accounting is divided into four stages which distinguishes the process by drifting management accounting from an integrated process right through the traditional, quantitative and mathematical processes. In particular management accounting systems in Japan, NIES and ASEAN are viewed in the light of the four stages. It is also emphasized that the steady establishment of financial accounting, particularly disclosure systems, play an important role in the progress of management accounting, by referring to a lesson from Japan.